Kinerja Organisasi Pemberdayaan Kesejahteraan Keluarga (PKK) dalam Pemberdayaan Perempuan di Kelurahan Mande - Nur Najmah (Jurnal Hukum dan Sosial Politik, 2023)
This study aims to determine: Performance of Working Groups (Pokja I, Pokja II, Pokja III, and Pokja IV) PKK Mande Village in implementing ten work programs related to women's empowerment.The type of research is descriptive quantitative. Data collection techniques used, namely: questionnaires, documentation, and interviews. The population in the study were the administrators and members of the PKK Mande Village, totaling 27 people, consisting of 14 administrators and 21 members. The sampling technique in this study used saturated sampling technique. The sample in this study were administrators and members of the PKK Mande Village, totaling 35 people. Data analysis techniques used in this study using descriptive statistical methods. The results of the research obtained, namely: 1) The performance of the Working Group (Pokja I) in implementing the work program of appreciation and practice of Pancasila and gotong-royong can be done very well. 2) The performance of Pokja II PKK Mande Village in implementing the skills education work program is very well implemented and the cooperative life development work program cannot be implemented. 3) The performance of Pokja III PKK Mande Village in implementing the food work program is very well implemented while the clothing and household management work programs are less well implemented.